Relasi antara sakralitas ritual peribadatan berjamaah dengan konfigurasi spasial arsitektur Masjid Sulthoni Plosokuning - Nadya Wicitra Paramitha; Purnama Salura (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
The relationship between sacred rituals of congregational worship and the spatial configuration of Sulthoni Plosokuning Mosque The design of current Mosque architecture has been found as a common phenomenon to have a similar design with other buildings such as office buildings, museums, monuments or even sculptures. The Mosque architecture, in fact, should not only accommodate pragmatic activities but also must have a spatial configuration related to the symbolic ritual activities that could stimulate the congregation’s awareness in entering the sacred space. The current research discusses the relationship between the sacred ritual of group worship and the spatial configuration of Mosque architecture. It aimed revealing how the sacred function of congregational rituals is correlated to the spatial configuration of Sulthoni Plosokuning Mosque and the specific aspects that become the indicators of the correlation. The analysis uses an elaboration of universal sacrality theory, the concept of rituals in Mosque architecture, architectural configuration theory, and architectural anatomy theory. The result of analysis showed that of the seven aspects of spatial configuration being discussed, four aspects were found to have dominant relationship with sacred ritual worship, three aspects had less dominant relations and one aspect has no relationship with the sacred ritual of worship. © 2020 Nadya Wicitra Paramitha, Purnama Salura